Informacinė mokslo integracija - Augustinaitis, Arūnas (Information & Media, 1994)
Recently in the modem society have appeared interdisciplinary information problems. They are the background for the new field of science - system of communication and information sciences, which covers all tendencies of information society. Information problems in humanities and social, technical, exact and natural sciences now is supposed as the background for integration of modem science and build up of the information paradigm of the science. The main theoretical body of the system of communication and information sciences are documentical communication sciences, because they deal with informatioo processes and build up interdisciplinary information research paradigms.